The Influence of Peer Behavior as a Function of Social and Cultural Closeness: A Meta-Analysis of Normative Influence on Adolescent Smoking Initiation and Continuation - Albarracín, Dolores (2017)
Although the influence of peers on adolescent smoking should vary depending on social dynamics, there is a lack of understanding of which elements are most crucial and how this dynamic unfolds for smoking initiation and continuation across areas of the world. The present meta-analysis included 75 studies yielding 237 effect sizes that examined associations between peers’ smoking and adolescents’ smoking initiation and continuation with longitudinal designs across 16 countries. Mixed-effects models with robust variance estimates were used to calculate weighted-mean Odds ratios. This work showed that having peers who smoke is associated with about twice the odds of adolescents beginning (OR = 1.96, 95% confidence interval [CI] [1.76, 2.19]) and continuing to smoke (OR = 1.78, 95% CI [1.55, 2.05]). Moderator analyses revealed that (a) smoking initiation was more positively correlated with peers’ smoking when the interpersonal closeness between adolescents and their peers was higher (vs. lower); and (b) both smoking initiation and continuation were more positively correlated with peers’ smoking when samples were from collectivistic (vs. individualistic) cultures. Thus, both individual as well as population level dynamics play a critical role in the strength of peer influence. Accounting for cultural variables may be especially important given effects on both initiation and continuation. Implications for theory, research, and antismoking intervention strategies are discussed